Ship 17 : a baris from Thonis-Heracleion - Belov, Alexander, (Oxford Center for Maritime Archaeology ;, 2019)
A study of the construction, structure and identification of Ship 17, a Late Period baris-vessel discovered during underwater excavations at Thonis-Heracleion, a sunken city in Aboukir Bay. Ship 17 is placed within the traditions of naval architecture both in Egypt and the wider Mediterranean.